Does public transit use increase the economic efficiency of urban areas? - Mathew Drennan; Charles Brecher (Journal of Transport and Land Use)
This paper explores the relationship between the scale of public transit services in urban areas of the U.S. and the efficiency of those economies, with efficiency measured by commercial office rents. Panel regressions are estimated in which real office rent is the left-hand variable. The key right-hand variable is per capita transit use. Other right-hand variables include demand for office space, office vacancy rate, average real wage and unemployment rate. Two-stage least squares equations are estimated to deal with possible simultaneity between office rents and transit use. Results indicate a positive relationship between public transit use and office rents. The relationship is stronger in areas with higher concentrations of office space in the central busines district; however, the estimated dollar impact of transit use on office rents is small.